MAKNA PESAN DAKWAH SYARIFAH HALIMAH ALAYDRUS MELALUI INSTAGRAM @halimahalaydrus - Camelia Putri Amalia; Mohamat Hadori; , Mokhammad Baharun (Fakultas Dakwah Universitas Ibrahimy, 2025)
The development of technology and information that is increasingly developing, presents social media. A number of da'is and da'iyah use Instagram media to spread religious messages. One of the da'iyah who is active in da'wah is Syarifah Halimah Alaydrus. Through the posting of photos/images containing da'wah messages in the form of beautiful words. This study uses a qualitative research method with a semiotic analysis approach of the Charles Sanders Pierce model. With @halimahalydrus Instagram account as the subject of the study. Meanwhile, the object of the research is about the da'wah message on the @halimahalaydrus Instagram account. The results of the analysis of this study show that the da'wah message on the Instagram account post @halimahalaydrus January 18 – February 21, 2024, namely: Maintaining speech and speech, Isra' Mi'raj, a harmonious household, and learning to get the pleasure of Allah Swt.